Pelatihan Balut Bidai Siswa PMR Wira SMA Negeri 2 Mataram - Alaydrus, M. Mukaddam; Taufik, Ahmad; Rahman , Hadian; Zulkarnaen, Decky Aditya; Hamzah, Muh. As'ad; Paerdoe, Lalu Dane Pemban (Jurnal Gema Ngabdi, 2025)
Traffic accidents frequently result in musculoskeletal injuries, particularly among school populations such as high school students. Members of the Youth Red Cross (PMR Wira) require adequate splinting and bandaging skills to provide initial management in the event of accidents occurring within the school environment. This community service activity aimed to enhance the splinting and bandaging competencies of PMR Wira students at SMAN 2 Mataram as a form of first aid for musculoskeletal injuries. The training method involved theoretical instruction and hands-on practice delivered to 29 students, with evaluation conducted through pre-test and post-test assessments. The results demonstrated a significant improvement in students’ knowledge and skills; the average score increased from 8.76 to 10.14, the standard deviation decreased from 1.480 to 1.093, and the minimum score rose from 6 to 8. A t-test indicated a significant difference (p < .001) between pre- and post-training outcomes. This training successfully strengthened the school’s first-aid system and contributed to creating a safer and more responsive school environment.